Relationships of familial sexual stigma and family support with internalized homonegativity among lesbian, gay and bisexual individuals: The mediating effect of self-identity disturbance and moderating effect of gender - Chung-Ying Lin; Mark D. Griffiths; Amir H. Pakpour; Ching-Shu Tsai; Cheng-Fang Yen (BMC, 2022)
Abstract Background The mediators of the association between familial attitudes toward sexual orientation and internalized homonegativity among lesbian, gay, and bisexual (LGB) individuals have not been well examined. Methods A cross-sectional survey study was carried out to examine the (i) associations of familial sexual stigma and family support with internalized homonegativity among young adult LGB individuals in Taiwan, and (ii) mediating effect of self-identity disturbance and the moderating effect of gender. Self-identified LGB individuals (N = 1000; 50% males and 50% females; mean age = 24.6 years) participated in the study. Familial sexual stigma, family support, self-identity disturbance, and internalized homonegativity were assessed. Structural equation modeling was used to examine relationships between the variables. Results The results indicated that familial sexual stigma was directly associated with increased internalized homonegativity, and indirectly associated with increased internalized homonegativity via the mediation of self-identity disturbance among LGB individuals. Family support was indirectly associated with decreased internalized homonegativity via the mediation of low self-identity disturbance. The direct association between family support and internalized homonegativity was only found among lesbian and bisexual women but not among gay and bisexual men. Conclusions Program interventions for familial sexual stigma, family support, and self-identity disturbance are warranted to help reduce internalized homonegativity among LGB individuals.